Diagnostic value of neutrophil to lymphocyte ratio, platelet to lymphocyte ratio and mean thrombocyte volume in irritable bowel syndrome-constipation according to Rome IV criteria - Akalin, Cagri; Canakci, Ebru (Annals of Medical Research, 2021)
Aim: Structural and biochemical reagents that could help diagnose irritable bowel syndrome (IBS) are still lacking. Moreover, use of certain diagnosis criteria in the diagnosis of the disease decreases the need for making over-diagnostic tests in order to rule out other diseases. Rome IV criteria include new parameters for the diagnosis of IBS. Our objective in this study is to research the diagnostic value of neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and mean platelet volume (MPV) count in IBS-Constipation (IBS-C).Material and Methods: Data of the cases among patients who applied to general surgery polyclinics of Ordu University Medical Faculty who were diagnosed with IBS and have Rome IV IBS-C diagnosis criteria. Healthy volunteers were selected from adult healthy patients who applied to general surgery policlinics of our hospital for general health check purposes. The age, sex, WBC (white blood cell), NLR, PLR, MPV values of the cases were analyzed. Results:Average age of IBS-C group was 39.47±9.97 (min 19-max 57). Average age of the control group was 40.16±11.50 (min 18-max 59). Out of 78 IBS-C group patients, 48 (61.5%) were women and 30 (38.5%) were men. Of 82 patients 54 (65.9%) were women, 28 (%34.1) were men. Average age of the patients was 39.83±10.75 (min 18-max 59). A significant result was obtained for NLR when control group was compared with IBS-C group (p=0.01). No significant difference was determined between two groups for MPV, PLR (p>0.05). Cut-off value of NLR was calculated as 1.895, and the sensitivity in IBS diagnosis was calculated as 51.3%, and the specificity was calculated as 59.8%. Conclusion: We have determined significant results with NLR, which is an inflammatory reagent, in IBS-C according to Rome IV Criteria. However, NLR has low sensitivity and specificity for IBS-C diagnosis from the other causes of constipation. We are of the opinion that inflammatory reagents such as NLR, PLR, MPV are not useful in the diagnosis of this disease. We consider that our study will shed a light on future studies with larger research populations.
Keywords: Rome IV criteria; irritable bowel syndrome; neutrophil to lymphocyte ratio (NLR); platelet to lymphocyte ratio (PLR); mean platelet volume (MPV).